Cassava yields set to double? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Within the next ten years it is possible that cassava yields could double. Improved~varieties that are being grown on farms across Africa yield about 20 tonnes per hectare. New varieties under trial at the International Institute of Tropical...